Akibat Hukum Yang Ditimbulkan Owner Dan Member Pada Praktik Arisan Online Sistem Menurun Atas Tidak Terpenuhinya Unsur Dalam Pasal 1348 KUH Perdata - Sri Mita Udin Soe (Jurnal Mahasiswa Kreatif, 2023)
This research is about juridical analysis of the application of article 1348 of the Civil Code to the practice of online arisan with a descending system. The method used in this research is normative. The purpose of this study is to find out the legal consequences caused by the Owner and Member of the Online Arisan Practice System for Decreasing the Non-fulfillment of Elements in Article 1348 of the Civil Code. The results of this study are that if one of the parties defaults or defaults, the provisions for sanctions are regulated in criminal and civil provisions, then the legal consequence is that if a member party does not complete the arisan contribution, the owner will bear the fee. so that members who commit defaults will hold negotiations/mediation efforts up to filing a lawsuit in court or carrying out a criminal law process by the owner as the person in charge of the arisan.